اسهامات اساليب التحليل المالي في استمرارية المؤسسة الاقتصادية - مقدم زين الدين; لعروسي محمد نزيه; زغيدي زياد (university of eloued جامعة الوادي, 2025)
تهدف ابراز إسهامات أساليب التحليل المالي ونماذج التنبؤ بالفشل المالي في دعم استمرارية المؤسسة الاقتصادية، وقد تم دراسة حالة شركة عموري للآجر خلال الفترة 2021–2024. وركزت على استخدام أدوات التحليل المالي (مثل النسب المالية، مؤشرات التوازن المالي) إلى جانب بعض نماذج التنبؤ بالفشل المالي، للكشف المبكر عن علامات التدهور المالي. وقد أظهرت نتائج التحليل أن الشركة تعاني من مؤشرات مالية مقلقة، أبرزها ضعف في الربحية وتراجع في نسبة المردودية وارتفاع نسبي في الديون، مما أدى إلى تدهور وضعيتها المالية ووضعها ضمن منطقة الخطر وفقًا لنماذج التنبؤ المعتمدة. وأكدت الدراسة أن غياب نظام فعال لمراقبة الأداء المالي، وعدم استخدام التحليل المالي كأساس لاتخاذ القرار، ساهما في تفاقم الوضع. لذلك، أوصت المذكرة بضرورة اعتماد أدوات التحليل والنماذج التنبؤية بشكل منهجي، وتعزيز كفاءة الجهاز المالي داخل الشركة، مع إعادة هيكلة التكاليف وتحسين استغلال الموارد، لضمان تجاوز مرحلة الخطر واستعادة الاستقرار المالي للمؤسسة. This study aims to assess the contributions of financial analysis techniques and financial distress prediction models in supporting the sustainability of economic enterprises. A case study was conducted on Amouri Brick Company over the period 2021–2024. The research focused on the application of financial analysis tools—such as financial ratios and financial equilibrium indicators—alongside selected financial failure prediction models, in order to enable early detection of financial deterioration signs. The results indicated that the company is exhibiting concerning financial indicators, notably weak profitability, declining return ratios, and a relatively high level of indebtedness. These issues have led to a deterioration of the company’s financial position, placing it within the “distress zone” as classified by the applied predictive models. The study concluded that the absence of an effective financial performance monitoring system, paired with the lack of utilization of financial analysis as a decision-making foundation, has contributed to the worsening situation. Accordingly, the report recommends the systematic adoption of analytical tools and predictive models, strengthening the financial management function within the company, restructuring costs, and improving resource utilization, in order to overcome the critical phase and restore the company's financial stability."
ماستر
Keywords: تحليل المالي،; الاستمرارية المالية; فشل المالي; نماذج التنبؤ.; s: Financial analysis; financial sustainability; financial distress; prediction models.